Pengaruh Organizations Climate dan Job Satisfaction Terhadap Turnover Intention PT Perkebunan Sumatera Utara - Muhammad Aidil Akbar Nasution Aidil Akbar; Sunaryo; Sopi Pentana (Jurnal Akutansi Manajemen Ekonomi Kewirausahaan (JAMEK), 2022)
This study aims to determine the effect of organizational climate and job satisfaction on turnover intention with organizational commitment as an intervening variable on employees of PT Perkebunan Sumatera Utara. The total population in this study amounted to 135 people, by using the total sampling method, the sample obtained was the total number of employees of PT. North Sumatra Plantation. The analysis technique used is path analysis. While the type of research used in this study is associative with a quantitative approach, the method used in this study is statistics with data collection techniques through questionnaires to all employees of PT. North Sumatra Plantation. The results showed that organizational climate had a positive and significant effect on organizational commitment of employees of PT Perkebunan North Sumatra. Job satisfaction has a positive and significant effect on organizational commitment of employees of PT Perkebunan North Sumatra. Organizations climate has a positive and significant effect on turnover intention in PT Perkebunan North Sumatra employees. Job satisfaction has no significant effect on turnover intention of PT Perkebunan Sumatera employees. Organizational commitment has no significant effect on turnover intention of PT Perkebunan North Sumatra employees. Organizational commitment has no effect on mediating organizational climate on turnover intention of PT Perkebunan North Sumatra employees. Organizational commitment has no effect mediating job satisfaction on turnover intention of PT Perkebunan North Sumatra employees.